Novel iron complexes bearing N6-substituted adenosine derivatives: synthesis, magnetic, 57Fe Mössbauer, DFT, and in vitro cytotoxicity studies - Trávnícek, Zdenek; Mikulík, Jirí; Cajan, Michal; Zboril, Radek; Popa, Igor (Bioorganic & medicinal chemistry, 2008)
Iron complexes (1-7) involving N6-benzyladenosine derivatives of the predominant composition [Fe(L(n))Cl(3)].H(2)O {where L(1)=N6-(2-fluorobenzyl)adenosine (1), L(2)=N6-(4-fluorobenzyl)adenosine (2), L(3)=N6-(2-trifluoromethylbenzyl)adenosine (3), L(4)=N6-(3-trifluoromethylbenzyl)adenosine (4), L(5)=N6-(4-trifluoromethylbenzyl)adenosine (5), L(6)=N6-(4-trifluoromethoxybenzyl)adenosine (6), and L(7)=N6-(4-chlorobenzyl)adenosine (7)} have been synthesized. The compounds have been characterized by elemental analysis, variable-temperature and in-field 57Fe Mössbauer, ES+ MS, FTIR, 1H and 13C NMR spectroscopies, magnetochemical and conductivity measurements, thermal (TGA/DSC/DTA) analyses, and DFT calculations. It has been found that the organic molecule is coordinated to iron via N7 atom of the appropriate adenosine derivative and the products are represented by mixtures of complexes with various iron oxidation (Fe(III)/Fe(II)) and spin states (S=5/2, 4/2, 3/2, 2/2) and geometries (tetrahedral or trigonal bipyramidal). It is caused by the fact that partial redox processes proceed during the reactions due to the presence of a ribose moiety, which is oxidized to the corresponding 5'-ribotic acid, and simultaneously, a portion of Fe(III) cations is reduced to Fe(II) ones. Moreover, a significant effect of crystal water molecules on stereochemistry, and hence, on magnetic and spectral properties of the prepared complexes has been found. The compounds have been tested for their in vitro cytotoxicity against the following human cancer cell lines: malignant melanoma (G-361), osteogenic sarcoma (HOS), chronic myelogenous leukemia (K-562), and breast adenocarcinoma (MCF-7). The most important results have been obtained for complex 2 with IC(50) values 8-16 microM against HOS, K-562, and MCF-7 cell lines, and for complex 6 with IC(50) value 4 microM against MCF-7 cell line.
Keywords: adenosin; Spectrophotometry, Infrared; Cell Line, Tumor; železo; magnetická rezonanční spektroskopie; Magnetic Resonance Spectroscopy; Inhibitory Concentration 50; algoritmy; Organometallic Compounds; Spectroscopy, Mossbauer; lidé; magnetismus; Iron; Magnetics; Humans; Spectrometry, Mass, Electrospray Ionization; spektroskopie Mossbauerova; Algorithms; hmotnostní spektrometrie s elektrosprejovou ionizací; inhibiční koncentrace 50; spektrofotometrie infračervená; nádorové buněčné linie; Adenosine; organokovové sloučeniny